Serviços ecossistêmicos culturais e praças públicas: análise da percepção de frequentadores da Praça da República em Belém-PA, Brasil - Pereira, Luanne Gabriela Barbosa (2025)
In cities where the impacts of pollution, climate change, and environmental challenges are increasingly intense, ecosystem services emerge as essential alternatives for promoting sustainability. Among these services, Cultural Ecosystem Services (CES) stand out, involving non-material benefits derived from nature, such as leisure, recreation, cultural identity, spirituality, and social interaction. In urban environments, green spaces like public squares play a fundamental role in providing these services to the population, directly reflecting on quality of life. In this context, Praça da República, located in Belém (Pará), represents an emblematic space, both for its historical and cultural value and its potential to offer CES to the urban population. This study aimed to analyze the perception of the square's visitors regarding the cultural ecosystem services provided, considering aspects such as events, use of space, infrastructure, comfort, and safety. The adopted methodology included a literature review, field visits, and the application of a structured questionnaire between November and December 2024, based on the concepts of Jan Gehl and the Active Design Guidelines, which emphasize the importance of the relationship between urban space and well-being. A total of 131 people participated in the survey, allowing for a qualitative analysis of user experience. The results revealed that most visitors to Praça da República are women, aged between 31 and 40, with a high school education. Visits occur mainly in the morning and on weekends, with activities such as strolling and shopping standing out. Although 84% of respondents value the thermal comfort provided by the square's vegetation, only 28% reported being satisfied with its quality. Safety was identified as the main challenge, being a priority for more than half of the participants, followed by the demand for cultural events and increased police presence. Significant structural problems were also identified: 63% expressed dissatisfaction with the available trash bins, and 47% pointed out issues with the square's general maintenance. The average qualitative perception of the space was 1.34 on a scale from 0 to 4, indicating an unsatisfactory evaluation due to current conditions such as damaged equipment, accumulated waste, and a general sense of insecurity. Nevertheless, 44% rated their experience in the square as “very satisfactory,” indicating the potential of the space to promote collective well-being. In conclusion, despite its weaknesses, Praça da República remains an important cultural and historical symbol, offering social interaction and a connection with nature in the heart of the urban area. However, for it to become a truly multifunctional, sustainable, and attractive space, more effective public actions are needed to improve infrastructure, safety, and participatory management. By enhancing Cultural Ecosystem Services, it is possible to promote the conscious and sustainable use of the square, strengthening its role in improving urban health and quality of life.